Analisis Tantangan Evolusi Transformasi dalam Pembangunan Infrastruktur Konstruksi sebagai Upaya Meningkatkan Pertumbuhan Ekonomi Bisnis: Studi Kasus PT. Adhi Karya (Persero) Tbk - Ananda Syahfitri; Yenni Samri Juliati (LPPM IAI Nasional Laa Roiba Bogor, 2023)
In achieving the company's goals there are many challenges in determining the success of the company. Over time, the evolution of transformation also witnessed the company's continued development or not. Business economic growth greatly determines the success of a company, both the quality of the policies implemented in the company and the high or low quality of its apparatus in the economic sector. The research method used is descriptive analysis with a qualitative approach. Information data collected from the Indonesia Stock Exchange (IDX).